Hygiene along the continuum of care in the early post-natal period: an observational study in Nigeria - Yolisa Nalule; Helen Buxton; Erin Flynn; Olutunde Oluyinka; Stephen Sara; Oliver Cumming; Robert Dreibelbis (BMC, 2020)
Abstract Background Newborns delivered in healthcare facilities in low- and middle-income countries are at an increased risk of healthcare associated infections. Facility-based studies have focused primarily on healthcare worker behaviour during labour & delivery with limited attention to hygiene practices in post-natal care areas and largely ignore the wide variety of actors involved in maternal and neonatal care. Methods This exploratory mixed-methods study took place in six healthcare facilities in Nigeria where 31 structured observations were completed during post-natal care, discharge, and the first 6 hours after return to the home. Frequency of hand hygiene opportunities and hand hygiene actions were assessed for types of patient care (maternal and newborn care) and the role individuals played in caregiving (healthcare workers, cleaners, non-maternal caregivers). Qualitative interviews with mothers were completed approximately 1 week after facility discharge. Results Maternal and newborn care were performed by a range of actors including healthcare workers, mothers, cleaners and non-maternal caregivers. Of 291 hand hygiene opportunities observed at health facilities, and 459 observed in home environments, adequate hand hygiene actions were observed during only 1% of all hand hygiene opportunities. Adequate hand hygiene prior to cord contact was observed in only 6% (1/17) of cord contact related hand hygiene opportunities at healthcare facilities and 7% (2/29) in households. Discharge advice was infrequent and not standardised and could not be remembered by the mother after a week. Mothers reported discomfort around telling non-maternal caregivers to practice adequate hand hygiene for their newborn. Conclusions In this setting, hand hygiene practices during post-natal care and the first 6 hours in the home environment were consistently inadequate. Effective strategies are needed to promote safe hand hygiene practices within the post-natal care ward and home in low resource, high-burden settings. Such strategies need to target not just mothers and healthcare workers but also other caregivers.